Effects of spatial uniformity of continuous and pulse laser irradiation on the microstructure and mechanical properties of Ti-6Al-4V in powder bed fusion - Moon, Seunghwan; Ji, Seungmuk; Ko, Yoonseok; Lee, Min-Su; Jun, Tea-Sung; Kim, Dong-Ik; Yeo, Jong-Souk (Elsevier BV, 2025)
Powder bed fusion of metals with laser beam (PBF-LB/M) using Ti-6Al-4V (Ti64) has enabled delicate fabrication of biocompatible medical implants. This research focuses on how the spatial uniformity of laser irradiation affects material under continuous wave (CW) and pulse width modulated (PWM) laser conditions, using a selfdeveloped PBF-LB/M system. The volumetric energy density (VED) was used as a reference parameter in order to accurately compare the effects of CW and PWM lasers, but limitations of VED, which does not include spatial and kinetic factors, which are reinforced in the PWM laser process, were also considered. Results revealed that the uniform distribution of energy irradiation across the entire region brought similar porosities and Vickers hardness tendencies for CW and PWM laser processes. In contrast, the spatially nonuniform energy transfer resulted in a significantly higher porosity in the specimen fabricated using the PWM laser than that produced using the CW laser at the same VED, reducing compressive yield strength. The electron backscattered diffraction analysis showed no significant differences in the average grain size, phase distribution, and misorientation angle of the samples produced using CW and PWM lasers under the same VED. However, sharper grains with an aspect ratio of less than 0.3 were 7 % higher in specimens produced using the PWM laser. This study highlights the possibility of controlling the microstructure and mechanical properties in a wider range when using the PWM laser with spatially nonuniform irradiation.